2020
DOI: 10.1016/j.cub.2020.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Assembly of Coordination Patterns in Human Infants

Abstract: Flexibility and generativity are fundamental aspects of functional behavior that begin in infancy and improve with experience. How do infants learn to tailor their real-time solutions to variations in local conditions? On a nativist view, the developmental process begins with innate prescribed solutions and experience elaborates on those solutions to suit variations in the body and the environment. On an emergentist view, infants begin by generating a variety of strategies indiscriminately and experience teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Hence, its presence in the first year of life is in line with the idea that complex functions do not need to be innate, as they can rather emerge from the early accumulation of evidence 5,34 , combined with powerful learning mechanisms 3 and fundamental attentional biases 35 . Recent theoretical and empirical work favours the idea that high-level cognitive systems can be generated via sub-symbolic dynamics 16,36 .…”
Section: Discussionsupporting
confidence: 62%
“…Hence, its presence in the first year of life is in line with the idea that complex functions do not need to be innate, as they can rather emerge from the early accumulation of evidence 5,34 , combined with powerful learning mechanisms 3 and fundamental attentional biases 35 . Recent theoretical and empirical work favours the idea that high-level cognitive systems can be generated via sub-symbolic dynamics 16,36 .…”
Section: Discussionsupporting
confidence: 62%
“…In addition to this online processing, we also conducted an offline reestimation of participants' bones for the recorded videos as accumulated 2D images because the online process was based on a best-effort format (i.e., changeable). This was motivated by a previous study that revealed toddlers' motor behaviors in similar offline motion analysis with their natural dynamics without wearing any devices 17 . As a result, we were able to show evidence of delicate changes in their reaching strategies where a preprocess of the children's noisy data was inevitable at first.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Openpose to extend the targeted body parts from the face to the whole body. Although Openpose detects bones from two-dimensional RGB images, it has been reported that its detection is reliable even for infants with much smaller body sizes 17 . As a result, we implemented augmented reality (AR) to display virtual marks in realtime on various body parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pose estimation has been used to study human locomotion [15,34,35] and provide kinematic measures such as lower limb joint angles; spatiotemporal measures such as gait speed, step length, and step time; and clinical ratings such as the Gait Deviation Index in patients with cerebral palsy or MDS-UPDRS gait scores for persons with Parkinson's disease. Other studies have used pose estimation to assess neuromotor risk and development in human infants [36,37]. These areas of application are introduced briefly here, but will be covered in greater detail in later sections of this manuscript.…”
Section: What Is Pose Estimation?mentioning
confidence: 99%